Maternal demographic and antenatal factors, low birth weight and preterm birth: findings from the mother and child in the environment (MACE) birth cohort, Durban, South Africa - Prakash M. Jeena; Kareshma Asharam; Aweke A. Mitku; Pragalathan Naidoo; Rajen N. Naidoo (BMC, 2020)
Abstract Background Low birthweight (LBW) and preterm birth (PB) remain the leading cause of morbidity and mortality in neonates worldwide. The aim of this study was to identify maternal demographic and antenatal factors associated with PB and LBW among low socio-economic communities. Methods Pregnant women (n = 1099) were recruited in the first trimester into the Mother and Child in the Environment (MACE) birth cohort in Durban, South Africa. Maternal factors such as demographic information, health status, residential area, occupational, personal and environmental smoking and biomass fuel use were obtained through standardised interviews, while clinical status was obtained in each trimester and antenatal information on HIV status and treatment, syphilis and conditions such as pregnancy induced hypertension, diabetes etc. was extracted from the antenatal assessments. Key outcomes of interest were preterm birth and low birthweight. The latter data was obtained from the clinical assessments performed by midwives at delivery. Logistic regression models identified factors associated with PB and LBW. Results Of the 760 live births, 16.4 and 13.5% were preterm and LBW, respectively. Mothers who delivered by caesarean section had an increased odds of having LBW babies (Adjusted odds ratio (AOR): 1.7; 95% CI: 1.1-2.7) and PB (AOR: 1.7, 95% CI: 1.1-2.7) versus normal vaginal deliveries. Mothers > 30 years (AOR: 1.8, 95% CI: 1.1-2.9) and current smokers (AOR: 2.7, 95% CI: 1.3-5.8) had an increased odds of having PB babies. Compared to younger mothers and non-smokers respectively. An effect of PB and LBW was seen among mothers with high BMI (25.0-29.9 kg/m2) (PB: AOR: 0.5, 95% CI: 0.3-0.9 and LBW: AOR: 0.5, 0.5, CI: 0.3-0.8), and obese BMI (> 30 kg/m2) (PB: AOR: 0.5, 95% CI: 0.3-0.9 and LBW: AOR: 0.4, CI: 0.2-0.7). Maternal HIV (PB AOR: 1.4 and LBW AOR: 1.2) and history of sexually transmitted infections (PB AOR: 2.7 and LBW AOR: 4.2) were not statistically significant. Conclusion Maternal age, cigarette smoking and caesarean delivery were associated with LBW and PB. Findings highlight the need of maternal health interventions to improve new-born health outcomes.